International research in graphene-oxide based materials for net-zero energy, military and aeronautic applications catalysed by Tamaulipas, Mexico: a mini review - Caballero-Briones, F.; Kaftelen-Odabasi, H.; Gnanaseelan, N.; Ruiz-Perez, F.; Tolentino-Hernandez, R. V.; Kamaraj, S. K.; Jimenez-Melero, E. (Frontiers Media Sa, 2023)
Graphene oxide, as a nanoscopic platform for functional materials, has been extensively studied for several applications. The present Mini Review stresses the collaborative research in graphene-oxide materials pivoted from the Group of Materials and Technologies for Energy, Health, and Environment at an Instituto Politecnico Nacional unit in Tamaulipas, in Northeastern Mexico, with Mexican, Turkish, and British collaborators. This review covers the recent works on photovoltaic and photocatalytic materials, coatings for thermonuclear reactors, and composites and metamaterials for military and aeronautic applications.
Keywords: graphene oxide; supercapacitors; photocatalytic hydrogen production; aeronautics; military